2010
DOI: 10.1021/pr100269b
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule-Based Inhibition of Histone Demethylation in Cells Assessed by Quantitative Mass Spectrometry

Abstract: Post-translational modifications on histones are an important mechanism for the regulation of gene expression and are involved in all aspects of cell growth and differentiation as well as pathological processes including neurodegeneration, autoimmunity, and cancer. A major challenge within the chromatin field is to develop methods for the quantitative analysis of histone modifications. Here we report a mass spectrometry (MS) approach based on ultra-performance high/low collision switching (UPLC-MS E ) to monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 51 publications
3
49
0
Order By: Relevance
“…These results suggested that in vivo DMOG administration can increase O 2 availability in inflamed colon tissue, and improved tissue oxygenation may contribute to the therapeutic effects of DMOG shown previously in mice with DSS-induced colitis [20,63]. demethylases) point towards multifunctional properties of this compound [20][21][22][23][24][25][26][27]. Inhibition of O 2 consumption by cells treated with DMOG has been reported previously [37][38][39].…”
Section: Effect Of Dmog On Respiration and Io 2 Of 3d Tissue Modelssupporting
confidence: 74%
See 1 more Smart Citation
“…These results suggested that in vivo DMOG administration can increase O 2 availability in inflamed colon tissue, and improved tissue oxygenation may contribute to the therapeutic effects of DMOG shown previously in mice with DSS-induced colitis [20,63]. demethylases) point towards multifunctional properties of this compound [20][21][22][23][24][25][26][27]. Inhibition of O 2 consumption by cells treated with DMOG has been reported previously [37][38][39].…”
Section: Effect Of Dmog On Respiration and Io 2 Of 3d Tissue Modelssupporting
confidence: 74%
“…As a PHD inhibitor, DMOG activates HIF-1 and NF-κB, playing a protective role in experimental model of colitis and diarrhoea [20,21], suppresses induced TNF-α expression [22] and abrogates TNF-α-induced intestinal epithelial damage [23]. On the other hand, DMOG was also reported to inhibit JHDM histone demethylases in 293T cells [24], similar to NOG [24][25][26]. Recently, DMOG was shown to activate AMPK signalling [27], which orchestrates global metabolic adaptation of cells to energy crisis and oxidative stress [28].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 95%
“…Deuterated acetic acid was one of the earliest reagents used to derivatize histones. 136 The derivatization adds a deuterated acetyl group to originally unmodified lysine residues. Because the acetyl groups contain deuteron instead of hydrogen, which causes a 3-Da mass shift, they therefore can be distinguished from endogenous acetylated lysine residue.…”
Section: Detection and Quantification Of Histone Ptmsmentioning
confidence: 99%
“…9 Yet, as a prodrug, the cytotoxic IC 50 of compound 2 (PD2) is in the millimolar range in cultured cells because of its poor cell-penetrating ability, 10 whereas 5-carboxy-8HQ, with a potent inhibitory effect on KDM4E in vitro (IC 50 = 0.2 μM), exhibits a relatively high cytotoxic IC 50 in HeLa cells (86.5 μM). 9 In this investigation, we determined the KDM4B· 2 ·H3K9me3 ternary complex structure and applied a structure-guided strategy to identify a selective inhibitor, 1,5-bis[( E )-2-(3,4-dichlorophenyl)ethenyl]-2,4-dinitrobenzene (NSC636819), toward KDM4A and KDM4B.…”
Section: Introductionmentioning
confidence: 99%